Mammography screening: Eliciting the voices of informed citizens. - Manja D Jensen; Kasper M Hansen; Volkert Siersma; John Brodersen (PLoS ONE)
Background Many medical organisations recommend continuing with existing mammography screening programmes but some recommend stopping or de-intensifying them. In Denmark women aged 50-69 are offered biennial mammograms free-of-charge. Objectives The aim of this study was to determine whether or not an informed public would recommend continuation of the Danish mammography screening programme, and to determine whether this recommendation was in line with what participants considered to be acceptable levels of mortality reduction and overdiagnosis. Methods A Deliberative Poll on mammography screening was held online in Denmark and 89 citizens participated. They were representative of the general population on sociodemographic parameters, attitudes towards and knowledge of mammography screening. Participants studied a video about the programme and took part in an online citizens' assembly where they deliberated with peers and experts in the field. All participants answered a survey at four time points: at recruitment; after video information; after deliberation, and a month after the assembly. Results Questionnaire data revealed that many participants were influenced by the deliberative polling process as 36%, changed their recommendation afterwards. At recruitment, 72% of participants strongly supported the continuation of mammography screening. This proportion was lower after the presentation of video information (55%), after deliberation (65%), and a month after the assembly (58%). Interestingly, these changes in recommendation were not correlated to changes in knowledge. The proportion of participants who recommended continuation following what they stated were acceptable rates of mortality reduction and overdiagnosis rose from 21% at recruitment to 40% after information and deliberation. Most participants (60%), therefore, made a recommendation that was not in line with levels of mortality reduction and overdiagnosis that they felt were acceptable. Conclusion After video information and deliberation participants were less supportive of the mammography screening programme compared to their immediate recommendation at the beginning of the process.